YOUTH DEPRESSION AND FUTURE CRIMINAL BEHAVIOR. (1st September 2014) - Anderson, D. Mark; Cesur, Resul; Tekin, Erdal
<x xml:space="preserve">Abstract</x> While the contemporaneous association between mental health problems and criminal behavior has been explored in the literature, the long‐term consequences of such problems, depression in particular, have received much less attention. Using data from the National Longitudinal Study of Adolescent Health (Add Health), we examine the effect of depression during adolescence on the probability of engaging in a number of criminal behaviors later in life. In our analysis, we control for a rich set of individual‐, family‐, and neighborhood‐level factors to account for conditions that may be correlated with both childhood depression and adult criminality. One novelty in our approach is the estimation of school and sibling fixed effects models to account for unobserved heterogeneity at the neighborhood and family levels. Furthermore, we exploit the longitudinal nature of our data set to account for baseline differences in criminal behavior. The empirical estimates show that adolescents who suffer from depression face a substantially increased probability of engaging in property crime. We find little evidence that adolescent depression predicts the likelihood of engaging in violent crime or the selling of illicit drugs. Our estimates imply that the lower‐bound economic cost of property crime associated with adolescent depression is approximately 227 million dollars per year. (JEL I10, K42)